Complete Comparison Display (CCD) evaluation of ethanol extracts of Centella asiatica and Withania somnifera shows that they can non-synergistically ameliorate biochemical and behavioural damages in MPTP induced Parkinson's model of mice. - Maheep Bhatnagar; Ishan Goel; Tathagato Roy; Sunil Dutt Shukla; Sukant Khurana (PLoS ONE)
Parkinson's disease remains as one of the most common debilitating neurodegenerative disorders. With the hopes of finding agents that can cure or reduce the pace of progression of the disease, we studied two traditional medicinal plants: Centella asiatica and Withania somnifera that have been explored in some recent studies. In agreement with the previous work on ethanol extracts of these two plants in mice model, we saw an improvement in oxidative stress profile as well as behavioral performance in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced Parkinson-like symptoms in Balb/c mice. Given the known potential of both the herbal extracts in improving Parkinson-like symptoms, we expected the combination of the two to show better results than either of the two but surprisingly there was no additivity in either oxidative stress or behavioural recovery. In fact, in some assays, the combination performed worse than either of the two individual constituents. This effect of mixtures highlights the need of testing mixtures in supplements market using enthomedicine. The necessity of comparing multiple groups in this study to get most information from the experiments motivated us to design a ladder-like visualization to show comparison with different groups that we call complete comparison display (CCD). In summary, we show the potential of Centella asiatica and Withania somnifera to ameliorate Parkinson's disorder.